2017
DOI: 10.1108/ijesm-11-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nature of rural energy transition in India

Abstract: Purpose The purpose of this paper is to explore the nature of rural energy transition in cooking options in India. Although India is aiming to achieve a double-digit economic growth, a large share of rural households still rely on firewood for cooking which not only has serious repercussions of increasing indoor pollution but also has a concomitant adverse effect on women and child morbidity and mortality. However, transition to clean energy options like improved cookstoves for these households may not be nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…Urmee and Gyamfi (2014) argue that programs aimed at the adoption of ICS fail when customers are afraid of using new technologies [5]. Similarly, Goswami et al (2017) report that trust in a new technology increases the probability of switching to ICS [77]. A positive attitude toward technology is usually associated with higher social class; for example, an interesting study conducted in India found that lower social classes are more likely to reject traditional technology than elites [39].…”
Section: Attitude Toward Technologymentioning
confidence: 99%
See 4 more Smart Citations
“…Urmee and Gyamfi (2014) argue that programs aimed at the adoption of ICS fail when customers are afraid of using new technologies [5]. Similarly, Goswami et al (2017) report that trust in a new technology increases the probability of switching to ICS [77]. A positive attitude toward technology is usually associated with higher social class; for example, an interesting study conducted in India found that lower social classes are more likely to reject traditional technology than elites [39].…”
Section: Attitude Toward Technologymentioning
confidence: 99%
“…As described by Tigabu (2017), positive reputation in terms of compatibility with the cooking culture of a community increases the use of ICS [86]. Cooking practices and taste/dietary preference related to the local culture are involved in decision making about ICS adoption [4,32,77,88]. In particular, some studies have found that attachment to the particular taste of food cooked on traditional stoves may act as a barrier to the adoption of LPG stoves [12,39,61,81], highlighting that it is not possible to prepare certain traditional dishes with ICS [88].…”
Section: Social and Cultural Influencesmentioning
confidence: 99%
See 3 more Smart Citations